Pengaruh Modal Kerja Dan Produktivitas Terhadap Profitabilitas Di Masa Pandemi Covid-19 - Eha Hasni Wahidhani; Dewi Fitrianti (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This study aims to build a decision-making model on the amount of working capital needed to increase business productivity so that it will ultimately increase sales turnover. It is expected that if the sales turnover increases, the company's profit will also increase. Working capital and work productivity of MSMEs as variables that affect the profitability or operating income. While the object of research used is MSME actors in the city of Bogor. This type of associative/correlative descriptive research. Arikunto (2006) states that correlative research is research that aims to find whether or not there is a relationship, how close the relationship is, and whether or not the relationship is meaningful. The population in this study are MSME actors spread across the city of Bogor. In this study, multiple linear regression analysis was not performed manually, but by using IBM SPSS Statistics Version 22. The results showed that there was a significant effect of working capital and productivity either partially or simultaneously or simultaneously on profitability. Keywords: Working capital, productivity, and profitability